Membangun Keterampilan Meronce Anak Panti Asuhan Mas Mansyur Malang Sebagai Langkah Gotong Royong Mewujudkan Generasi Indonesia Emas Tahun 2045 - Diyah, Maulidiyah Aulia Rahma; Arsila Dwi Lestari; Dinda Nur Fadila; Nayla Fadillah Febrianty; Yusuf Waishol; Andra Arema Saputra; Muchamad Arryan Naufal Putra; Muhammad Iqbal Maulana; Nailul Insani (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
This beading activity aims to develop the skills, character, and creativity of children at Mas Mansyur Orphanage. This research employed a descriptive qualitative method by conducting observations at Mas Mansyur Orphanage in Malang City on 10 children aged 5–14 years. The beading activity received positive responses from the children, with both boys and girls actively participating in creating rings and bracelets from beads. This activity had positive impacts, such as fostering perseverance and precision. Additionally, the social interactions during the activity strengthened solidarity and mutual cooperation among participants. The activity concluded with the writing and presentation of aspirations, which were written on origami paper. This was expected to build self-confidence in pursuing dreams and instill hope and determination in the children. The conclusion of this study is that this activity effectively develops the children’s technical skills, mental resilience, and character while instilling essential life values